2005
DOI: 10.1080/10810730590934217
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Information Needs in Rural Areas

Abstract: Although cancer presents obstacles for all who experience it, persons in rural communities must negotiate additional challenges. This study determined the cancer information (CI) needs and the CI-seeking behavior and preferences among rural-dwelling persons. Patients (N = 801) = 50 years of age seen in 36 rural Kansas primary care practices completed a Cancer Care Information Needs Survey (CCINS); physicians completed a cancer resource knowledge and preference survey. Of the 801 patients, 184 (23%) reported a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 17 publications
0
22
0
1
Order By: Relevance
“…Previous research indicates that many rural patients are medically underserved (e.g., Engelman et al, 2005). They often do not have the same degree of access to comparable health services as breast cancer patients from more populated areas.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research indicates that many rural patients are medically underserved (e.g., Engelman et al, 2005). They often do not have the same degree of access to comparable health services as breast cancer patients from more populated areas.…”
Section: Discussionmentioning
confidence: 99%
“…The most noteworthy finding in the reviewed studies was that participants face challenges related to service provision in their rural communities. Of the 23 studies reviewed, 10 articles revealed service provision challenges such as lack of access to cancer information, limited access to professional or hospital assistance, and isolation from professional support or other supportive services were enduring challenges (Clavarino et al, 2002;Duggleby et al, 2010;Engleman, Perpich, Peterson, Hall, & Ellerbeck, 2005;Fitch et al, 2003;Gray, James, Manthorne, Gould, & Fitch, 2004;McConigley et al, 2011;McGrath, 2001;Rogers-Clark, 2002;Wilkes, White, & Riordan, 2000;Wilkes, White, Mohan, & Beale, 2006).…”
Section: Continued On Page 161…mentioning
confidence: 99%
“…In general, physicians serve as the primary source of medical information [1,2] and the communication between doctor and patient is of critical importance to quality decision making [3][4][5], even although it can be challenging for both parties. Our previous research raised concerns about the adequacy of physician-patient communication regarding information relevant to patient decision making and values among patients with advanced cancer [6].…”
Section: Introductionmentioning
confidence: 99%